Typology of Student Learning in Qira’ah Subject with Multiple Intelligence Perspective - Muid, Abdul; Ilmiani, Aulia Mustika; Fikri, Ahmad (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2021)
This study tries to reveal the typology of student learning in Qira'ah subjects, the Multiple Intelligence of students in these subjects, and the relationship between student learning typology in Qira'ah subjects from the perspective of Multiple Intelligences. The Subjects in this study were students of the Jam'iyah Ihsaniyah al-Mukhtariyah Kerinci Islamic Boarding School. This research uses qualitative and quantitative methods. The results showed that the type of student learning in Qira'ah subjects consisted of Auditory learning types, followed by Visual learning types and some students had Kinesthetic learning styles. The intelligence possessed by students when taking Qira'ah lessons is Linguistic or Verbal intelligence which functions to utilize language to communicate. Visual Intelligence is useful for analyzing facts and realities that are seen directly and Kinesthetic Intelligence to directly capture the material. In the Qira'ah subject at the Jam'iyah Ihsaniah al-Mukhtariyah Kerinci Islamic Boarding School, students' learning styles are closely related to multiple intelligences to develop directed and effective learning abilities and processes.